Multi-Omics and miRNA Interaction Joint Analysis Highlight New Insights Into Anthocyanin Biosynthesis in Peanuts (Arachis hypogaea L.) - Li, Jiawei; Ma, Yucong; Hu, Mengdie; Zhao, Yulu; Liu, Bin; Wang, Chunmei; Zhang, Min; Zhang, Liping; Yang, Xinlei; Mu, Guojun (Frontiers in Plant Science, 2022)
Peanut (Arachis hypogaea L.) is one of the most important economic and oil crops in the world. At present, peanut varieties with rich anthocyanin in testa are rare in the market, but the selection and breeding of varieties with the related traits has always attracted the attention of breeders. In this study, two peanut varieties with the pink and purple testa, G110 (G) and Z18-40 (Z) were used to conduct interaction joint analysis of multi-omics and miRNA-target gene. The anthocyanin content of Z18-40 was 7.49-8.62 folds higher than G110 on 30 DAF (days after flowering) and 45 DAF via liquid chromatography tandem mass spectrometry (LC-MS/MS). And then, a total of 14 candidate genes related with the anthocyanin biosynthesis were identified for correlation in different comparison groups (R2 ≥ 0.80), among of a novel gene Ah21440 related with hydroxycinnamoyl transferase (HCT) biosynthesis was identified. In addition, Cyanidin 3-O-glucoside (Kuromanin, pmb0550) was the only common differentially accumulated metabolite (DAM) identified using multi-omics joint analysis in G1_vs_G2, Z1_vs_Z2, G1_vs_Z1 and G2_vs_Z2, respectively. Correlation analysis of miRNA-target genes and DEGs in the transcriptome shows that, AhmiR2950, AhmiR398, AhmiR50 and AhmiR51 regulated to HCT and chalcone biosynthesis related candidate genes (Ah21440, arahy. UDJX6I, arahy. TJ3PHW). Lastly, all of 14 candidate genes were validated using quantitative real-time PCR (qRT-PCR), which trends were consistent with that of the former transcriptome data. The results provide important reference for in-depth research on the anthocyanin metabolism mechanism in peanut testa.